The service innovation handbook action-oriented creative thinking toolkit for service organizations : templates-cases-capabilities - Kimbell, Lucy (BIS Publishers, 2014)
Shows how understanding user and customer experiences by analyzing ethnographic and big data, combined with exploratory prototyping, helps businesses design innovative services. Focuses on the early stages of a design project and discusses conceptual and practical challenges involved in creating service ecosystems that address organizational and societal issues. Includes examples from start-ups, big corporations, policy contexts and social innovation.